THE EFFECTIVENESS OF GIVING BANANA HULL POC AND FERTILIZER COW MANURE ON THE GROWTH AND PRODUCTION OF PEANUT (Arachis hypogeae L) - Irwansyah, Irwansyah; Refnizuida, Refnizuida; Z.N.A., Hanifah Mutia (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Efforts to improve the peanut cultivation system (Arachis hypogaea L) need to be done to increase peanut productivity in order to reduce imports. One way that can be done is by using organic materials such as POC banana hump and cow dung fertilizer. This study aims to determine the effect of giving POC banana weevil and cow dung fertilizer on the growth and production of peanuts (Arachis hypogaea L). This research was conducted at Jln. Milkfish, East Binjai District, North Sumatra by using a factorial randomized block design consisting of the first factor, namely the provision of banana weevil POC (P) consisting of 3 levels, namely P0 (0 liters/plot), P1 (1 liter/ liters of water/plot). ) and P2 (1 liter/liter of water/Plot). The results showed that the application of POC banana weeds had no significant effect on all observation parameters and cow dung had a very significant effect on wet peanut production per sample and wet peanut production per plot but had no significant effect on plant height parameters, number of leaves, number of pods. per sample and number of pods per plot. From the application of cow dung fertilizer to the production of peanut plants, the best was in K3 (3 kg/plot) and the lowest production of peanuts was in k0 (0 kg/plot).